Influence of Seed Priming and Coating on Seed Longevity in Greengram (Vigna mungo L.) cv.CO 8 - K MALARKODI (Seed Research, 2026)
The greengram cv.CO 8 seeds were imposed with various treatments viz., seed priming by adopting seed to solution ratio of 1:1 (T2), seed coating with TNAU seed coating polymer @ 4g kg-1 of seed (T3) and seed priming + seed coating (T2 +T3 = T4 ). The treated seeds were packed in super bag and cloth bag and stored under ambient condition along with untreated control seeds (T0). During storage period the seeds were evaluated for quality parameters at bimonthly interval. The result revealed that primed, coated and combined treatment (primed + coated seed) maintained more than 75% germination [above Indian Minimum Seed Certification Standards (IMSCS)] even after 20 months of storage study period compared to control both in super bag and cloth bag under ambient condition.